Digital Privacy Laws – Evolution and Consumer Perceptions among online users in India - Bathia, Amit (Journal of International Commercial Law and Technology, 2025)
As India rapidly embraces digital technologies, concerns surrounding data privacy and the protection of personal information have become increasingly significant. This study explores the progress of digital privacy laws in India and assesses consumer perceptions and awareness among Indian online users regarding data protection. With the proliferation of internet usage, particularly through social media, digital banking, and mobile applications, individuals are frequently exposed to risks such as impersonation, phishing, romance scams, and data breaches. Notwithstanding the introduction of critical legislative frameworks—including the Information Technology Act (2000), its 2008 amendment, and the Digital Personal Data Protection Act (2023)—public understanding and engagement with these laws remain restricted. To evaluate user awareness, a structured online survey was conducted with 153 respondents from diverse demographic backgrounds. Findings reveal that over 70% of respondents lacked awareness of existing data privacy laws, frequently consented to terms without understanding, and showed uncertainty about their rights and remedies. The study also categorizes key types of cybercrimes prevalent in India and contextualizes them within the broader policy landscape. Challenges such as low digital literacy, complex consent mechanisms, limited outreach, and government surveillance concerns are also addressed. This paper contributes by tracing India’s legislative progress on data privacy, identifying user-level gaps, and offering actionable recommendations to enhance awareness, promote informed consent, and strengthen the digital ecosystem. It concludes by emphasizing the need for a multi-stakeholder approach involving government, industry, and civil society to create a privacy-aware and digitally resilient population. Future research directions are also proposed, focusing on mechanisms for improving transparency, regulatory adaptation, and consumer empowerment in the digital age.
ISME
Keywords: Digital privacy; Consumer perceptions; Data privacy laws; Cybersecurity; Data protection; Data protection policies